Engineering Applications of Biochar - Huang, Wu-Jang (IntechOpen, 2017)
This book has included the following major sections: "Introduction", "History of Biochar," "Preparation of Biochar," and "Applications of Biochar." The editor and authors hope that the development of biochar can cross its application field from agriculture into engineering.